Respon penggunaan bakteri penambat nitrogen Rhizobium sp dan pupuk kohe ayam - Suryani Sajar; Andi Setiawan (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2023)
This study aims to determine the effect of Nitrogen-inhibiting bacteria and chicken manure (cohe) fertilizer on soybean yield. The research method used a 2 factorial Randomized Group Design. The first factor was the treatment of rhizobium biofertilizer (R) consisting of 4 levels, namely R0 = 0 g/kg seed, R1 = 5 g/kg seed, R2 = 10 g/kg seed, and R3 = 15 g/kg seed. The second factor is the treatment of chicken cohe fertilizer (S) consisting of 4 levels, namely S0 = 0 kg/m2, S1 = 0.5 kg/m2, S2 = 1.0 kg/m2, and S3 = 1.5 kg/m2. The results showed that the provision of rhizobium biofertilizer 10 g/kg seed had a real effect on the number of soybean pods, dry weight of seeds per plant, dry weight of 100 seeds, with the highest number of pods 1169.03 g, the highest dry weight of seeds 388.56 g, the highest weight of 100 seeds 15.88 g. Application of chicken cohe fertilizer 1.5 kg/m2 on the soil had a real effect on the number of pods, dry weight of seeds per plant, dry weight of 100 seeds, with the highest number of pods 167.25 g, dry weight of seeds 393.86 g and the highest weight of 100 seeds 16.50 g. The interaction of rhizobium biofertilizer and chicken cohe fertilizer was not significantly different in all treatments.